Fabrication and Characterization of Polysulfone-Graphene Oxide Mixed Matrix Membranes for the Natural Gas Treatment - R. Bakhshi; M. Moraveji; A. Parvareh (Iranian Journal of Chemical Engineering)
The polysulfone mixed matrix membranes (MMM) with different concentrations of graphene oxide (0, 0.25, 0.5 wt % of the polymer) are fabricated by a phase separation method. The cross-sectional structures and their upper surface were assessed by the (SEM) surface roughness of the membranes assessed by (AFM). The mechanical and thermal stability of the fabricated membranes were evaluated as well. The separation of Carbon dioxide, nitrogen and methane from natural gas was considered. Also, by increasing the concentration of graphene oxide in the polymer matrix, the thickness of the spongy structure increases and the holes of the finger-like membranes are also destroyed. From the cross-sectional images of the outer surface of the MMM, it was concluded that an active selector layer was created on the lower surface of the membrane. The membrane tensile strength and the length of the membrane at fracture point increased slightly with an increase in the concentration of graphene oxide. Transition Glass temperature of the membrane increased by the addition of graphene oxide to the structure. From TGA analysis, in the presence of graphene oxide, the thermal stability improved. From the gas permeation test, by the addition of 0.25 % of graphene oxide to the polymer, CO2 permeability was increased from 61.22 GPU to 76.04 GPU, while the addition of 0.5 wt % resulted in a lower permeability (69.55 GPU). The Nitrogen gas permeation flux of membranes decreased from 10.93 GPU to 3.91 GPU by the addition of 0.50 wt % of graphene oxide. The Methane gas permeation flux is reduced from 11.31 GPU to 6.95 GPU and 4.92 GPU by the addition of 0.25 % and 0.50 % of graphene oxide respectively. In conclusion, an increase in the concentration of graphene oxide increased the carbon dioxide selectivity.